2016
DOI: 10.4315/0362-028x.jfp-15-570
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Elimination of Human Norovirus in Food and on Food Contact Surfaces: A Critical Review

Abstract: This critical review addresses the persistence of human norovirus (NoV) in water, shellfish, and processed meats; on berries, herbs, vegetables, fruits, and salads; and on food contact surfaces. The review focuses on studies using NoV; information from studies involving only surrogates is not included. It also addresses NoV elimination or inactivation by various chemical, physical, or processing treatments. In most studies, persistence or elimination was determined by detection and quantification of the viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 99 publications
2
50
0
Order By: Relevance
“…However, virus behavior is very type-specific and thus, there is a need to identify a large number of surrogates and improve detection methods to allow quantification following application of control measures. A recent review of NoV even suggested discontinuing all surrogate studies unless direct comparison between surrogate and NoV inactivation kinetics is established (Cook et al, 2016). The recent propagation system described for human NoV (Ettayebi et al, 2016) opens the possibility to develop more appropriate risk assessment models and recommendations for adequate processing technologies.…”
Section: Challenges For Validationmentioning
confidence: 99%
“…However, virus behavior is very type-specific and thus, there is a need to identify a large number of surrogates and improve detection methods to allow quantification following application of control measures. A recent review of NoV even suggested discontinuing all surrogate studies unless direct comparison between surrogate and NoV inactivation kinetics is established (Cook et al, 2016). The recent propagation system described for human NoV (Ettayebi et al, 2016) opens the possibility to develop more appropriate risk assessment models and recommendations for adequate processing technologies.…”
Section: Challenges For Validationmentioning
confidence: 99%
“…; Cook et al . ). In an effort to determine infectivity through molecular methods, Nuanualsuwan and Cliver () suggested the use of a combined proteinase K and RNase pretreatment applied to heat‐, chlorine‐ and UV‐inactivated viruses (HAV, poliovirus‐1 and feline calicivirus).…”
Section: Introductionmentioning
confidence: 97%
“…Typical procedures for water and food disinfection include heat treatment, UV radiation and free chlorine, but the lack of true knowledge on the ratio between infectious and noninfectious viral particles has hindered the assessment of the efficacy of disinfection. Different approaches have been suggested and tested, including integrated cell culture PCR, enzymatic treatment (RNase), viability PCR, detection of whole or specific region of the viral genome and porcine gastric mucin qPCR (Hamza et al 2011;Knight et al 2013;Cook et al 2016). In an effort to determine infectivity through molecular methods, Nuanualsuwan and Cliver (2002) suggested the use of a combined proteinase K and RNase pretreatment applied to heat-, chlorine-and UV-inactivated viruses (HAV, poliovirus-1 and feline calicivirus).…”
Section: Introductionmentioning
confidence: 99%
“…Once deposited on surfaces, human NoV can remain infectious for several weeks (Escudero et al, 2012; Lopman et al, 2012; Hall et al, 2014). Environmental stability of human NoV is enhanced by resistance to commercial sanitizers and disinfectants, including alcohol-based hand sanitizers and hypochlorite at regulated concentrations (Liu et al, 2010; Tung et al, 2013; Cromeans et al, 2014; Cook et al, 2016). These unique traits of human NoV contribute to the high number of outbreaks observed annually in close quarter environments such as cruise ships, long-term care facilities, and schools, as well as in association with food service (Lopman et al, 2012; Cook et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental stability of human NoV is enhanced by resistance to commercial sanitizers and disinfectants, including alcohol-based hand sanitizers and hypochlorite at regulated concentrations (Liu et al, 2010; Tung et al, 2013; Cromeans et al, 2014; Cook et al, 2016). These unique traits of human NoV contribute to the high number of outbreaks observed annually in close quarter environments such as cruise ships, long-term care facilities, and schools, as well as in association with food service (Lopman et al, 2012; Cook et al, 2016). Therefore, innovative methods for inactivation of NoV from these environments where frequent human contact with surfaces is expected are needed to control the spread of the pathogen.…”
Section: Introductionmentioning
confidence: 99%